Preface - Ruiz-Hitzky, Eduardo; Aranda, Pilar (Recent Patents on Nanotechnology, 2012)
It is a great pleasure for us to address these words in the 5th anniversary of Recent Patents on Nanotechnology (NANOTEC) with which, we would like to congratulate to all the authors, reviewers, past and present Editorial Board Members, the Bentham people involved in the NANOTEC production, as well as readers, whom have made possible that NANOTEC was indexed and abstracted (ISI Web of Knowledge, Thomson Reuters) for the first time, reaching a 0.949 impact factor in 2010. Nanotechology is clearly interesting from the point of view of basic research but it also deals with the development of new materials, devices, or other systems in which the unique properties and behavior afforded by the nanometric scale open way to a world of wonders in which researchers and technologists need to shear experience for enlarging the current knowledge. In this way, NANOTEC intends to provide a platform for this purpose and brings out the opportunity to learn about nanotechnology in relation to their applications and their implications in the current and future society. Therefore, papers in these years have addressed issues not only related to the latest approaches applied for developing new materials with dimensions on the nanoscale but also to the use of nanotechnology in medicine, electronics, biomaterials, energy production and other fields of application. At the same time, it is also clear that nanotechnology, as any new technology, raises other concerns with special relevance in those related to toxicity and environmental impact of nanomaterials, and such issues have been also addressed in our Journal. We hope that in the next years the journal will continue increasing its impact and the readership. Finally, we would like to thank Bentham Science Publishers for appointing us as Chiefs of the Editorial Board of the journal, and also acknowledge the kind assistance of the entire Bentham team, and lately to Ms. Humera Sharif, who have helped us in these years in managing the journal.